2011
DOI: 10.1016/j.bbmt.2010.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Acute Gastrointestinal Graft-versus-Host Disease in Pediatric Patients: Serum Albumin on Day 5 from Initiation of Therapy Correlates with Nonrelapse Mortality and Overall Survival

Abstract: The aim of the present study was to identify factors associated with the risk of development of gastrointestinal acute graft-versus-host disease (GI-aGVHD), as well as to evaluate the impact of various baseline parameters on response to treatment, nonrelapse mortality (NRM), and overall survival (OS) in pediatric patients with GI-aGVHD after allogeneic hematopoietic stem cell transplantation (allo-SCT). We retrospectively analyzed 300 pediatric patients who underwent allo-SCT from HLA-matched related or volunt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 33 publications
0
17
0
Order By: Relevance
“…One study demonstrated that a >0.5 g/dl decrease in serum albumin level from pretransplantation to the onset of aGVHD predicts the development of grade III–IV disease . In addition, low albumin levels at day +5 after transplant were predictive of lower overall survival among patients with gut GVHD . Although both malnutrition and inflammation are known to decrease serum albumin levels, its relationship with GVHD is poorly understood and warrants additional investigation .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…One study demonstrated that a >0.5 g/dl decrease in serum albumin level from pretransplantation to the onset of aGVHD predicts the development of grade III–IV disease . In addition, low albumin levels at day +5 after transplant were predictive of lower overall survival among patients with gut GVHD . Although both malnutrition and inflammation are known to decrease serum albumin levels, its relationship with GVHD is poorly understood and warrants additional investigation .…”
Section: Discussionmentioning
confidence: 99%
“…11 In addition, low albumin levels at day +5 after transplant were predictive of lower overall survival among patients with gut GVHD. 7 Although both malnutrition and inflammation are known to decrease serum albumin levels, its relationship with GVHD is poorly understood and warrants additional investigation. 12 We had relatively few patients with low baseline serum albumin, and it was not an independent risk factor for TA B L E 5 Adjusted longitudinal analysis of nutritional status and risk of GVHD within the subsequent 30-day period aGVHD or mortality.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations